‘Learning her culture and growing up strong’: Aboriginal and/or Torres Strait Islander fathers, children and the sharing of culture - Prehn, Jacob; Guerzoni, Michael Andre; Peacock, Huw (My University, 2020)
Indigenous fathers play a central role in the lives of Indigenous children growing up strong. For Australia’s Indigenous people, growing strong includes the possessing heightened levels of health, education and cultural knowledge. This article focuses on Indigenous fathers and how they understand the importance of sharing cultural activities with their children. We argue that the sharing of Indigenous cultural practices, and the subsequent telling of this narrative, are key enablers for Indigenous fathers to assist their families to flourish. We analyse qualitative data from the Longitudinal Study of Indigenous Children to explore what components/aspects of Indigenous culture fathers perceive will assist children to strongly mature, how culture is transmitted, and what barriers fathers face in this process. Results show that according to participants, learning about culture, family and identity are components to helping children prosper, with collecting food the most common activity used to achieve this end.
Journal of Sociology
Keywords: Childhood and child development; Culture and language; Families and relationships; Identity